Why are Australian Universities Doing So Well in the Rankings? - Locke, William (International Higher Education, 2020)
Australian universities appear to be doing well in the latest versions of the most influential global rankings, for example doubling their representation in the Times Higher Education World Reputation Rankings’ top 100. How have they done this, and is this a sudden improvement or a longer term trend? More importantly, is this sustainable, given increasing competition and government ambivalence toward higher education?